A Study of Monomyth Subversion in the Novel Arthas: Rise of the Lich King - Dzurinathif, Ajimas; Litaay, Adeline Grace Marianne (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study discusses the subversion of Joseph Campbell’s monomyth structure in a novel written by Christie Golden entitled Arthas: Rise of the Lich King. In most stories following the monomyth, the hero goes through three main stages: Departure, Initiation, and Return. These stages usually show the hero growing as a person and bringing something valuable back to help others. However, Arthas Menethil’s journey in the novel takes a different path. Using Campbell’s theory and an intrinsic literary approach, this study looks at how Arthas changes from a noble prince into a dark and feared figure known as the Lich King. Instead of learning wisdom or becoming a better person, Arthas becomes more obsessed, loses his morality, and turns away from the people he once wanted to protect. The analysis shows how the novel uses the monoymyth stages but changes its purpose, from a story of growth and enlightenment to one of downfall and destruction. The findings reveal how the novel repurposes the monomyth into a tale of obsession, moral collapse, and the rejection of reintegration. This study helps to understand how stories can break away from traditional patterns to explore deeper themes like failure, corruption, and the making of a villain.